1991
DOI: 10.1063/1.1142315
|View full text |Cite
|
Sign up to set email alerts
|

rf driven multicusp H− ion source

Abstract: An rf driven multicusp source capable of generating 1-ms H− beam pulses with a repetition rate as high as 150 Hz has been developed. This source can be operated with a filament or other types of starter. There is almost no lifetime limitation and a clean plasma can be maintained for a long period of operation. It is demonstrated that rf power as high as 25 kW could be coupled inductively to the plasma via a glass-coated copper-coil antenna. The extracted H− current density achieved is about 200 mA/cm2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…From this compact source, an H À current density greater than 250 mA/cm 2 has been extracted. 139 In 1991, Leung et al 140 reported the development of an RF-driven H À ion source at LBNL for use in the superconducting super collider. In a later publication, Leung 141 presented the advantages of the RF-driven source over the dc filament discharge source:…”
Section: Volume Negative Ion Sources For Accelerator Applicationsmentioning
confidence: 99%
“…From this compact source, an H À current density greater than 250 mA/cm 2 has been extracted. 139 In 1991, Leung et al 140 reported the development of an RF-driven H À ion source at LBNL for use in the superconducting super collider. In a later publication, Leung 141 presented the advantages of the RF-driven source over the dc filament discharge source:…”
Section: Volume Negative Ion Sources For Accelerator Applicationsmentioning
confidence: 99%
“…In recent years continuously pumped D-D generators, which use radiofrequency (RF) driven ion sources [7] for generating high beam currents and beam-loaded Titargets [6], have been developed at the Lawrence Berkeley National Laboratory (LBNL) [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Employing a magnetic filter to reduce the electron temperature near the outlet made filament driven Tandem sources more competitive in 1982 [12]. Introducing a Cs collar and replacing the filament with an RF driven antenna in 1990 promised to overcome the lifetime limitation of filaments [13]. For significant average plasma powers, the antennas need to be water-cooled and electrically isolated from the conductive plasma.…”
Section: The Successful Internal Antennasmentioning
confidence: 99%
“…For significant average plasma powers, the antennas need to be water-cooled and electrically isolated from the conductive plasma. LBNL developed antennas that featured only a single, thin layer of porcelain [13], which kept failing at high plasma powers [14,15]. Listing six reasons why internal antennas could never work reliably [16], DESY developed an external antenna source that was very successful at low duty cycles, but was never used for production [17].…”
Section: The Successful Internal Antennasmentioning
confidence: 99%